Biological Predictors of Postpartum Depression: A Literature Review - Leonard Chandra Parasian (HM Publisher, 2021)
Introduction. Maternal mental health problems pose major public health challenges for societies across the globe. PPD affects between 13–19% of women worldwide and has negative consequences on the woman herself and on her entire family. PPD has negative consequences on the woman herself and on her entire family. Biological models of PPD can be conceptualized as withdrawal models that concern the fact that reproductive hormones and stress hormones rise dramatically prior to delivery. A few studies have attempted to identify biological aspect as a predictor of PPD. Method: Searches were conducted in PubMed. The following keywords were applied in the database during the literature search: “Postpartum Depression” OR “Postnatal Depression” OR “Puerperal Depression” AND “Predictor”. Study was considered if they were published between January 2010 and August 2021, English language journals. 34 articles were identified. Abstracts were reviewed by researcher and 4 were eliminated. The researcher then reviewed full text of the remaining 26 articles. After full text review, an additional 15 articles did not meet inclusion criteria. The total of 10 articles were identified that met inclusion and exclusion criteria. Result: Partial reviews are available that cover biological processes broadly, with emphasis on the endocrine system, the immune system and genetic factors. Endocrine system includes estrogen, progesterone, prolactin, oxytocin, and testosterone. For stress hormone take a part like corticotropic releasing hormone, adrenocorticotropic hormone, β-Endorphin, cortisol, dan catecholamine. The cytokine and C-reactive protein are a group of immune system. The latter is serotonin, MAO-A, estrogen receptor, oxytocin, glucocorticoid, and brain derived neurotropic factor. Conclusion: Postpartum depression is a common but treatable condition. Appropriate and timely treatment is crucial in order to help women cope with their situation and reduce the devastating consequences. It is likely that the dramatic hormonal changes occurring in the postnatal period also play a significant role in the etiology of PPD, but the exact nature of these influences remains unknown, and needs further research.